The urbanization pattern, economic growth, CO2 gas emissions and land transportation intensity - Nur Aini Hidayati, Almara S., (Opción, 2020)
This research focuses on the effect of CO2 gas emissions, urbanization and economic growth on the transportation intensity in Indonesia. Econometric analysis with Vector Error Correction Model shows that there is a difference in results of the long-term assessment and short-term effects. Changes to CO2 gas emissions, urbanization and economic growth were responded to fluctuate. If the three variables increase by 1%, the transportation intensity will increase varies according to the type of variable, including CO2 gas emissions, urbanization, and economic growth. We conclude that CO2 gas emissions, urbanization and economic growth affect the transportation intensity in the positive direction.